(untitled) (Ilm fan taraqqiyotida raqamli iqtisodiyot va zamonaviy ta’limning o’rni hamda rivojlanish omillari, 2025)
Abstract. Oral translation, often referred to as interpreting, is a dynamic and multifaceted communicative activity that transcends the simple substitution of words between two languages. While linguistic competence is undoubtedly fundamental, the effectiveness of an interpreter relies heavily on a complex interplay of extralinguistic features. These features encompass the cultural, social, cognitive, and situational factors that shape the interpretation process and ultimately determine the accuracy, fluency, and appropriateness of the delivered message. Neglecting these extralinguistic dimensions can lead to misunderstandings, misinterpretations, and ultimately, a breakdown in communication. This article aims to delve into the intricate world of extralinguistic features in oral translation, examining their impact and highlighting their crucial role in ensuring successful cross-cultural communication.